Pengembangan Aktivitas Gerak Berbasis Modifikasi Permainan untuk Meningkatkan Kemampuan Keterampilan Motorik pada Anak Sekolah Dasar - Erick Salman; Helvi Darsi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to produce a motor learning module through game modification in elementary school children and can be used by sports and health physical education teachers (PJOK) in learning. This research is a development research (education research and development (R & D) with the Dick and Carey model approach. There are 7 steps of the Dick and Carey model, namely: (1) development of information in the field; (2) analysis information; (3) developing the initial product (draft module); (4) expert validation and revision; (5) small-scale field trials and revisions; (6) large-scale field trials and revisions; and (7) making the final product. used in this development research, namely: (1) interviews; (2) teacher observations; and (3) questionnaires. Data analysis techniques used qualitative and quantitative descriptive analysis. The results showed that: (1) validation results obtained from Expert experts obtained 80.1% (2) small-scale trials on 12 grade III students at SD Negeri 51 Lebong obtained 75.3%; (3) large-scale product trials on 40 grade III and IV students at SD Negeri 32 Lebong obtained 78 , 5%; (3) m the developed toothpaste is categorized as good in improving children's motor skills. In conclusion, the motion activity module through game modification can improve motor skills in elementary school children and is feasible to be applied to learning. Keywords: Movement Activities, Motor Skills, Game Modification